Lymphocyte apoptosis in acute respiratory syncytial virus bronchiolitis - ROE, M F E (Blackwell Science Inc, 2004)
Respiratory syncytial virus (RSV) infection may have an effect on the development of T cell memory responses. RSV bronchiolitis in infants is associated with a transient decline in circulating lymphocytes. We hypothesized that the mechanism underlying this lymphopenia is apoptosis. Blood was taken from 32 infants during primary RSV bronchiolitis and three months later. Using flow cytometry, we found that absolute numbers of both CD3+/CD4+ T-helper lymphocytes (P = 0·029) and CD3+/CD8+ cytotoxic lymphocytes (CTL) (P = 0·043) were significantly reduced during acute infection. Up-regulated expression both of Fas (P < 0·001) and tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) receptor (P < 0·001) was found during acute illness on both CD3+/CD4+ and CD3+/CD8+ lymphocytes, when compared with convalescent samples. Expression of Fas on CD4+ lymphocytes was inversely related to CD4+ number (P = 0·03). Plasma levels of soluble Fas ligand (P = 0·028) and caspase-1 (P = 0·037), determined by enzyme-linked immunosorbent assay, were increased during bronchiolitis. Plasma interleukin-18, a product of caspase-1 activity, was not raised. Taken together, these data suggest that in acute RSV infection, CD4+ helper lymphocytes and CD8+ cytotoxic lymphocytes are primed to undergo apoptosis. This is a mechanism through which lymphopenia may occur and T cell memory may be altered.